Clinical characteristics and diagnosis of the COVID-19 in patients in COVID outpatient clinics - Petrov Kiurski, Miloranka; Živanović, slavoljub (General Practice, 2022)
Objective. Examine clinical manifestations, PCR testresults, and visit outcomes in patients in COVID-outpatientclinics.Method. The survey was performed using the questionnaire,in February 2021. in patients in four COVID-outpatientclinics in Belgrade and one in Subotica. We got the data abouttheir jobs, gender, age, present symptoms and comorbidities,PCR-testing, and visit outcomes. The data were processed usingthe software statistical package SPSS 17. Statistical significancewas defined for level p
Keywords: COVID-19 symptoms; PCR test; visit outcome; general medicine